Evaluation of Antibacterial Activity of Combined Ethanolic Extracts from Callistemon citrinus Leaves and Mangifera indica Bark Against Streptococcus pneumoniae - Rubayiza P; Mukisa R (Journal of Experimental Pharmacology)
Paul Rubayiza, Robert Mukisa School of Pharmacy, Department of Pharmaceutical Chemistry & Analysis, Kampala International University-Western Campus, Bushenyi, UgandaCorrespondence: Paul Rubayiza, Email rubayizapaul@kiu.ac.ug; rubayizapaul2@gmail.comBackground: Streptococcus pneumoniae is a leading cause of respiratory infections, including pneumonia, meningitis, and otitis media. The rise in antimicrobial resistance has complicated treatment strategies, highlighting the need for alternative therapies. Plant-based remedies are increasingly being explored for their antibacterial potential, particularly in traditional medicine.Methods: This study evaluated the antibacterial activity of ethanolic extracts from Mangifera indica bark and Callistemon citrinus leaves, individually and in combination, against S. pneumoniae. The agar well diffusion method was employed to assess zones of inhibition. A combination effect was analyzed by calculating the increase in fold area of inhibition.Results: Both individual extracts demonstrated antibacterial activity. However, the combination of the two extracts produced larger zones of inhibition than either extract alone. The calculated increase in fold area of inhibition was 0.659, suggesting a synergistic effect.Conclusion: The combination of Mangifera indica and Callistemon citrinus extracts shows enhanced antibacterial efficacy against S. pneumoniae, supporting their traditional use in managing respiratory infections. Further research is needed to determine the mechanism of action, in vivo efficacy, and safety profile before clinical application.Keywords: Callistemon citrinus leaves, Mangifera indica bark, Streptococcus pneumoniae, antibacterial effect